Delamanid susceptibility testing of Mycobacterium tuberculosis using the resazurin microtitre assay and the BACTEC™ MGIT™ 960 system. (13th April 2016) - Schena, Elisa; Nedialkova, Lubov; Borroni, Emanuele; Battaglia, Simone; Cabibbe, Andrea Maurizio; Niemann, Stefan; Utpatel, Christian; Merker, Matthias; Trovato, Alberto; Hofmann-Thiel, Sabine; Hoffmann, Harald; Cirillo, Daniela Maria
Abstract: Objectives: The objective of this study was to develop standardized protocols for rapid delamanid drug susceptibility testing (DST) using the colorimetric resazurin microtitre assay (REMA) and semi-automated BACTEC™ MGIT™ 960 system (MGIT) by establishing breakpoints that accurately discriminate between susceptibility and resistance of Mycobacterium tuberculosis to delamanid. Methods: MICs of delamanid were determined by the MGIT, the REMA and the solid agar method for 19 pre-characterized strains. The MIC distribution of delamanid was then established for a panel of clinical strains never exposed to the drug and characterized by different geographical origins and susceptibility patterns. WGS was used to investigate genetic polymorphisms in five genes ( ddn, fgd1, fbiA, fbiB and fbiC ) involved in intracellular delamanid activation. Results: We demonstrated that the REMA and MGIT can both be used for the rapid and accurate determination of delamanid MIC, showing excellent concordance with the solid agar reference method, as well as high reproducibility and repeatability. We propose the tentative breakpoint of 0.125 mg/L for the REMA and MGIT, allowing reliable discrimination between M. tuberculosis susceptible and resistant to delamanid. Stop codon mutations in ddn (Trp-88 → STOP) and fbiA (Lys-250 → STOP) have only been observed in strains resistant to delamanid. Conclusions: We established protocols for DST of delamanid in the MGIT and REMA, confirming their feasibility in routine TB diagnostics, utilizing the same discriminative concentration for both methods. Moreover, taking advantage of WGS analysis, we identified polymorphisms potentially associated with resistance in two genes involved in delamanid activation.